A mortality cohort study in a north Italian aircraft factory. Issue 10 (October 1989) - Costa, G; Merletti, F; Segnan, N
Abstract : Mortality in a cohort of 8626 workers employed between 1954 and 1981 in an aircraft manufacturing factory in northern Italy was studied. Total follow up was 132, 042 person-years, with 76% accumulated in the age range 15 to 54. Median duration of follow up from the date of first employment was 16 years. Vital status was ascertained for 98.5% of the cohort. Standardised mortality ratios were calculated based on Italian national mortality rates. Altogether 685 deaths occurred (SMR = 85). There was a significant excess of mortality for melanoma (6 cases, SMR = 561). Six deaths certified as due to pleural tumours occurred. No significant excess of mortality was found in specific jobs or work areas.